Epidemiological Study on Helminth Infestations in Buffaloes (Bubalus bubalis) in Andhra Pradesh - Anusha, Makkena; Veerendra, Uppalapati (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Gastrointestinal (GI) parasitic infestations pose a significant threat to livestock, leading to production losses, poor health, and even death, resulting in substantial economic losses for farmers. This study aimed to detect helminth parasitic infestations in buffaloes in Andhra Pradesh, India, and to examine, how these infestations vary by age, gender, and season. A total of 331 GI tracts from buffaloes processed at the Local Municipality Slaughterhouse in Vijayawada were examined over a period of one-year. Out of these, 228 tracts (68.9%) were found positive for various helminth parasites. The most prevalent parasite was Amphistomes (18.12%), followed by Schistosoma spindale (12.08%), Setaria spp. (15.4%), Cysticercus tenuicollis (5.43%), Monezia spp. (5.13%), Cooperia spp. (3.32%), Trichuris spp. (3.04%), Haemonchus spp. (2.11%), Gigantocotyle (1.20%), Bunostomum spp. (1.2%), Fasciola (0.90%), and Stilesia spp. (0.9%). The study also found that younger buffaloes (1 to 2.5 years old) had a higher infestation rate (73.11%) compared to older buffaloes, who had a prevalence rate of 61.34%. Female buffaloes had a significantly higher infestation rate of 96.96% compared to males (58.38%). Seasonal variations were observed, with 23.24% infestation in summer, 44.73% during the rainy, and 32.01% in winter season. This investigation showed that gastrointestinal (GI) parasitic infestations are widespread and occur at a relatively high rate in buffaloes of Andhra Pradesh causing severe economic loss to the farmers by reducing the overall productivity.
Keywords: Andhra Pradesh; Buffalo; Gastrointestinal parasites; Slaughter house; Vijayawada